Cryogenic forming of AA6065 by ECAP. (2022) - Arunprasath, K.; Sudhan, J.; Kavitha, S.; Paramasivan, S.; Vijayakumar, M.
Abstract: Due to the difficulty of deforming high-strength aluminium alloys, the use of traditional Spartan plastic deformation procedures, concept that supports the creation of extremely fine granular microstructures and higher strength. The use of cryogenic Equal Channel Angular Pressing (ECAP) deformation as an alternate method of deforming a 6065 alloy is investigated in this study. A tool with a 90° internal angle is utilised here. Cryogenic ECAP (followed by proper temperature treatments) outcomes in higher deformation, strength, and ductility, according to our findings. To demonstrate that cryogenic forming can enhance the characteristics such as high aluminium alloys, early outcomes on the effects of cryogenic Equal Channel Angular Pressing on micro - structure and mechanical characteristics changes in the 6065 alloy. Due to the alloy's increased strain-hardening capabilities, low deformation temperatures improve ductility and workability. It was possible to perform up to three Equal-Channel Angular Pressing passes without strain localization or cracking at 610 °C using various cumulative plastic stresses.